Spirituality in pediatric palliative care: a scoping review protocol (Research, Society and Development, 2021)
Objective: This study aims to describe the protocol and methodology used to carry out a scope review that will map the scientific evidence on spirituality in the context of pediatric palliative care. Methodology: This is a scope review that will be developed according to the recommendations of the Joanna Briggs Institute (JBI). For the writing of the study, the PRISMA Extension for Scoping Reviews (PRISMA-ScR) will be used. A comprehensive search will be carried out in the Web of Science, Scopus, Cochrane Library, PubMed, CINAHL and EMBASE databases, in addition to the gray literature search in the Google Scholar, ProQuest and OpenGrey databases, without limitation as to year of publication and language. In addition, an additional search for articles will be performed by reading the references of the studies included in the review. Primary and secondary studies that address spirituality in the context of pediatric palliative care will be included, regardless of the type of design. Documents such as letters, comments, editorials and opinion articles will be excluded. The selection of studies by reading the titles, abstracts and full text will be conducted by two independent reviewers. Data extraction will be performed using a form built by the authors based on JBI recommendations. Data will be organized, summarized and analyzed for extent, nature, distribution and recurring patterns, and the results will be communicated narratively and through network maps. Final considerations: It is expected that the results from this scope review can contribute to strengthening the use of spiritual care for children under palliative care, with the scope of promoting a better quality of life for them and their families. Additionally, it is intended through this research to encourage health professionals to meet this dimension during the care of children under palliative care, with a view to providing humanized care and quality spiritual assistance that can help them in their search for a meaning for life, in relieving pain and making it easier to deal with the anguish and fear that permeate this process.